2007
DOI: 10.1111/j.1468-3083.2007.01926.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Demodex folliculorum density in haemodialysis patients with a control group

Abstract: Despite the presence of sebaceous gland atrophy in haemodialysis patients, the higher density of DF in these patients than controls supports the supposition that this mite can increase immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 21 publications
0
16
1
1
Order By: Relevance
“…Finally, there are numerous reports of cases of demodicosis in immunosuppressed people and animals. Demodicosis has been reported, for instance, in patients with primary immunodeficiency, human immunodeficiency virus infection, renal transplant, haemodialysis and rheumatoid arthritis . Rosacea‐like eruptions or demodicosis has also been reported after treatment with glucocorticoids, calcineurin inhibitors (tacrolimus, pimecrolimus) and epidermal growth factor receptor inhibitors …”
Section: Immunology Of Canine Demodicosismentioning
confidence: 99%
“…Finally, there are numerous reports of cases of demodicosis in immunosuppressed people and animals. Demodicosis has been reported, for instance, in patients with primary immunodeficiency, human immunodeficiency virus infection, renal transplant, haemodialysis and rheumatoid arthritis . Rosacea‐like eruptions or demodicosis has also been reported after treatment with glucocorticoids, calcineurin inhibitors (tacrolimus, pimecrolimus) and epidermal growth factor receptor inhibitors …”
Section: Immunology Of Canine Demodicosismentioning
confidence: 99%
“…[20]. Similarly Duzgun et al [21] also reported higher mean mite density in hemodialysis patients than controls.…”
Section: Discussionmentioning
confidence: 80%
“…However, it might be speculated that the prevalence of D. canis ‐positive puppies is higher than that reported in adults due to the incomplete function of the immune system at a very young age, allowing proliferation of mites. In adults, with adequate immune system function, control mechanisms might limit the population of mites, as hypothesized in humans 22 …”
Section: Discussionmentioning
confidence: 99%